2013
DOI: 10.1016/j.jvs.2013.02.249
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endovascular aneurysm repair on renal function compared with open repair

Abstract: After EVAR, there is a continuous decline in renal function with respect to OR, regardless of fixation level and independently of pre-existing renal insufficiency. The risk of GFR impairment after EVAR should be taken into consideration in selecting patients with preoperative renal insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 28 publications
1
38
2
1
Order By: Relevance
“…The reported incidence of AKI within 30 days or during hospitalization after EVAR varies between studies in the literature, likely because of heterogeneity in the definitions used, and ranges from 3.1% to 18.8%. 16,[28][29][30][31] Recent studies by two groups led by Saratzis and Pirgakis utilized the AKIN criteria to define postoperative AKI in patients who underwent EVAR and reported an incidence of 18.8% and 17%, respectively, compared with 9.4% in our cohort. 16,31 Also, in contrast to the findings reported by Saratzis et al, we found that both decreased preoperative eGFR level and length of surgery were independent predictors of AKI.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The reported incidence of AKI within 30 days or during hospitalization after EVAR varies between studies in the literature, likely because of heterogeneity in the definitions used, and ranges from 3.1% to 18.8%. 16,[28][29][30][31] Recent studies by two groups led by Saratzis and Pirgakis utilized the AKIN criteria to define postoperative AKI in patients who underwent EVAR and reported an incidence of 18.8% and 17%, respectively, compared with 9.4% in our cohort. 16,31 Also, in contrast to the findings reported by Saratzis et al, we found that both decreased preoperative eGFR level and length of surgery were independent predictors of AKI.…”
Section: Discussionmentioning
confidence: 77%
“…Nevertheless, another retrospective cohort comparing EVAR with aortic open repair showed that a postoperative deterioration in kidney function at 30 days was observed in 13% of patients after EVAR and persisted at long-term follow-up, with a 11% reduction in estimated glomerular function following EVAR at nine years. 30…”
Section: Discussionmentioning
confidence: 99%
“…The endovascular procedure was performed in the operating room by two experienced vascular surgeons under either general or epidural anesthesia. We used sufentanile (0.3-0.5 mg/kg) and propofol (1-2.5 mg/kg) for induction of general anesthesia and remifentanile (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) mg/kg/h) and propofol (6-8 mg/kg/h) for maintenance. Epidural anesthesia was performed with a loss of resistance technique and injection of approximately 10 mL of ropivacaine 1% and 10 mg sufentanile, followed by repetitive administration of 1 to 2 mL Ropivacaine 1%.…”
Section: Methodsmentioning
confidence: 99%
“…However, the influence of EVAR on postoperative renal function remains a controversial topic. [4][5][6][7] Although it is generally accepted that renal function declines over time after EVAR, whether postoperative renal dysfunction is attributable to EVAR or simply to the progressive effects of aging or existing comorbidities is debatable. Further, the influence of stent graft fixation type on renal outcomes remains controversial.…”
mentioning
confidence: 99%